Automatic System Balancing Using Special Protection Scheme, ROCOF and Under Frequency Protection (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a power system the generation has to be equal to the demand. If not, the system cannot be said to operate under effective condition. Suppose a sudden change occurs in load, it will be reflected in change in frequency. This can be determined by Rate of Change of Frequency (ROCOF). In Madakkathara, there are three 220kV feeders each can carry a maximum current of 750A.When load increases current exceeds beyond a limit, the person who used to monitor the current in the meter will open the feeder to reduce the current. This paper uses ROCOF to detect the frequency change in voltage and current from current transformer and potential transformer and the lines will be opened automatically by sending a trip signal to the respective relays. The frequency can be measured by detecting the zero crossing of voltage and current.